2012
DOI: 10.1584/jpestics.d12-027
|View full text |Cite
|
Sign up to set email alerts
|

Dispersible silica nanoparticles as carrier for enhanced bioactivity of chlorfenapyr

Abstract: Pesticides are being used in agriculture to control pests for better yield and production. However, due to evaporation, rain waste-out, photodegradation, hydrolysis and other factors, most pesticides are lost before they reach their targets.1) Extensive quantities of pesticides are used to compensate for the losses that lead to serious environmental pollution and human toxicity.1,2) An e ective way to solve these problems is nanotechnology. e increase in the surface to volume ratio and surface energy of nanope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 9 publications
1
31
0
2
Order By: Relevance
“…A novel formulation based on silica NPs has also been proposed for improving the effectiveness and slowing the release of the pro‐insecticide chlorfenapyr, with promising results. Field tests showed that the insecticidal activity associated with silica NPs was at least twice that of chlorfenapyr, associated with microparticles or without particles, and the insecticide release was slowed down to over 20 weeks, providing high‐localized concentration over a long period …”
Section: Nanomaterials In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…A novel formulation based on silica NPs has also been proposed for improving the effectiveness and slowing the release of the pro‐insecticide chlorfenapyr, with promising results. Field tests showed that the insecticidal activity associated with silica NPs was at least twice that of chlorfenapyr, associated with microparticles or without particles, and the insecticide release was slowed down to over 20 weeks, providing high‐localized concentration over a long period …”
Section: Nanomaterials In Agriculturementioning
confidence: 99%
“…Field tests showed that the insecticidal activity associated with silica NPs was at least twice that of chlorfenapyr, associated with microparticles or without particles, and the insecticide release was slowed down to over 20 weeks, providing high-localized concentration over a long period. 13 Mesoporous silica nanoparticles (MSNs) are synthetic particles possessing well defined and tuneable pore sizes (2-50 nm), large pore volumes, high surface areas with easily-modifiable surface properties, chemical stability, resistance to microbial attack, tailorable nanostructures, biocompatibility, and aqueous degradability. 14,15 Moreover, MSN protect loaded active ingredients (AIs) against enzymatic degradation as no swelling or changes in porosity occur in response to external stimuli, such as pH and temperature.…”
Section: "Inert Nanomaterials"mentioning
confidence: 99%
“…Las nanoemulsiones permiten mejorar la dispersión y absorción del ingrediente activo y hasta incrementan su toxicidad (Kookana et al, 2014;Chinnamuthu y Boopathi, 2009). Song et al, (2012) evaluaron el incremento de la toxicidad del clorfenapir (un insecticida y acaricida de uso agrícola) a través de la utilización de nanopartículas de sílice como portador. Tanto en sus estudios de laboratorio como de campo, observaron que la toxicidad para los insectos se duplicó con respecto a la formulación a nivel micro.…”
Section: Outlook On the Use Of Nanomaterials In The Pesticides Formulunclassified
“…Nanoemulsions allow to improve dispersion and absorption of the active ingredient and even to increase its toxicity (Kookana et al, 2014;Chinnamuthu and Boopathi, 2009). Song et al, (2012) evaluated the increase of toxicity of chlorfenapyr (an insecticide and acaricide of agricultural use) throungh thw utilization of nanoparticles of silica as carrier. Both in their laboratory and field studies they observed that toxicity for insects doubled in respect to micro formulation.…”
Section: Outlook On the Use Of Nanomaterials In The Pesticides Formulmentioning
confidence: 99%
“…Recently, numerous studies have focused on silica nanoparticles (SNPs) use in pesticides [10]. They have been shown to be high stability, chemical versatility, biocompatibility, and low cost have potential as nano-pesticide delivery system for agro-biotechnological applications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%